The category of "health": the main concepts and methods of evaluation in physical education in comprehensive educational establishments - Sidorchenko E.N (Kharkov National Pedagogical University, 2010)
The statistical data on a level of health of schoolboys are resulted. It is specified, that only 10 % of schoolboys can be considered healthy. Others of 90 % - have these or those deviations in a state of health. The category "health" in several aspects is surveyed: psychogienic, somatic, physical and social. It is confirmed, that a heredity, a bionomics, chemicalization, conditions of life, the condition and an opportunity of health services variously influence health of the person. As criteria of a level of health use characteristics of acclimatization, a homeostasis, a reactivity.